“CINTA”, Pembelajaran Al-Quran Komprehensif Berbasis Contoh, Irama, Nazham, Tartil, dan Alat Bantu Pembelajaran - Agus Nur Qowim (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Innovation in learning the Qur'an has developed along with the progress of the times. It is undeniable that various methods of reading the Qur'an are present and offered to improve the capabilities of modern humans in relation to the ability to read the Qur'an. However, there are still various gaps so that learners still have difficulty in achieving a degree of completion in reading the Qur'an. Based on a survey of several research institutions, the results show that the ability to read the Qur'an of the Indonesian people is relatively low. Only 44.57% of Indonesians are categorized as being able to read the Qur'an fluently. These facts and concerns inspired the author to present a thought about the method of learning the Qur'an which is abbreviated as CINTA. The method used in this study is a qualitative method with a descriptive research approach. CINTA is a Al-Quran learning method based on giving examples, mastering rhythm, using nazham, based on tartil rules, and equipped with supporting tools and media. With CINTA, it is hoped that the Muslim community at large can achieve the target of completing reading the Qur'an. CINTA is a comprehensive Qur'an learning that will minimize reading errors due to examples of readings from teachers. With CINTA, learning the Qur'an will run enthusiastically with the teaching of Rhythm, Nazham and the use of tools that will lead someone to complete reading the Qur'an.